The Impact of Board Characteristics and Product Diversification on Firm Performance of Real Estate Industry in China - Li, Shuojing (2019)
The purpose of this study is to examine the relationship between board characteristics, product diversification and firm performance as well as the moderator effect of board characteristics on product diversification by applying several panel data linear regression models with Driscoll-Kraay standard errors. The sample consists of 106 real estate companies listed in China from 2013 to 2018. The result shows that a certain board size could bring benefits to a company, but once the size exceeds the critical point, the interests of shareholders would be damaged. CEO duality has a negative influence on firm performance. The presence of independent directors has not been found in any association with firm performance, which is the same as board meetings. Besides, product diversification can be said not to have contributed to improving the firm value. In addition, this study indicates that the board size has a negative moderating effect on product diversification and firm performance. However, the study fails to find any moderating effect of CEO duality and independent directors on the relationship between product diversification and firm performance. The results indicate that corporate performance is the result of different factors. Firm-specific factors, including firm size and debt ratio, also affect firm performance as well.